Low Dose Dabigatran-Induced Severe Pulmonary Hemorrhage and Cardiogenic Shock, Salvaged by Reversal Agent and Extracorporeal Membrane Oxygenation - Fu, Chih-Chun; Chen, Ying-Cheng; Yang, Bing-Jung; Chen, Ching-Pei (Archives of Clinical and Medical Case Reports, 2020)
A 67-year-old man with newly diagnosed posterior mitral leaflet flail and atrial fibrillation was given dabigatran for stroke prevention upon admission. Within 12 hours of taking two doses of 110 mg dabigatran, the patient suffered from severe pulmonary hemorrhage, acute respiratory failure, and cardiogenic shock. He was rescued by a single dose of 5 g idarucizumab in addition to extracorporeal membrane oxygenation (ECMO) support. The patient recovered to stable hemodynamic status then successfully underwent surgical intervention for mitral valve repair. He was discharged 2 weeks after surgery.